USE OF LIGNIN SEPARATED FROM BIO-OIL IN ORIENTED STRAND BOARD BINDER PHENOL-FORMALDEHYDE RESINS - Badamkhand Sukhbaatar; Philip H. Steele; Moon G. Kim (BioResources, 2009)
Bio-oil produced from fast pyrolysis of biomass has been investigated as a renewable fuel and as a source of industrial chemicals. The lignin fraction of bio-oil produced from wood in our fast pyrolysis reactor was separated by using only water and methanol with a 25% yield based on bio-oil weight. This separation procedure appears to be of lower cost than the reported extraction procedure using ethyl acetate as solvent. The isolated pyrolytic lignin was smoothly incorporated into phenol-formaldehyde resins at 30%, 40%, and 50% phenol replacement levels, and the resultant resins were evaluated as oriented strand board core-layer binders. The evaluation results indicated that the pyrolytic lignin is effective for up to about 40% replacement of phenol in synthesizing wood adhesive type PF resins.